Assessment of cardiopulmonary resuscitation knowledge and experiences between emergency department nurses hospital pre and post basic life support training course, Egypt (Annals of Medical Research, 2021)
Aim: Determination of the effect of training CPR program on the nurses working practice and knowledge in Emergency department (ED). Nearly 20% survive rate in adult of hospital cardiac arrest (CA). Cardiopulmonary Resuscitation (CPR) is increase the survival rate into double number but CA without treatment is falling 10–15% per minute of survival rate; however, the performed proper CPR likely shifts this curve towards a higher probability of survival.Material and Methods: The study is Interventional included 65 nurses. They fill questionnaire sheet used and constructed via the Research Committee in Murcia’s Hospital based on the “American Heart Association (AHA) 2010 Guidelines of CPR”. To assess nurses’ knowledge about sudden cardiac arrest and CPR but we used Pre and post questionnaire knowledge that applied in three phases: Assessment phase, Implementation phase, and Evaluation phase.Results:The study revealed 73% of nurses do not have previous training. Twenty-seven percentage nurses not have any information about CPR and 22.5% of them the main source of the information gained through training program more than one year ago. While the 94.6% of them willing to attend CPR training program and report they need to perform high quality CPR respectively.Conclusion: The study give a clear view of the current knowledge and practice of CPR among nursing staff in our institution and can help in developing it. It also gives detailed information about the exact weak points, which would improve, in next workshops.
Keywords: Skill programme; cardiopulmonary resuscitation; nurses staff.